Some N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted) ureido/thioureido]benzenesulfonamides as carbonic anhydrase I and II inhibitors - Türk, Sevda; Tok, Fatih; Çelik, Hülya; Karakuş, Sevgi; Nadaroğlu, Hayrunnisa; Koçyiğit-Kaymakçıoğlu, Bedia; Küçükoğlu, Kaan (My University, 2017)
In the present study, N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substitue)ureido] benzenesulfonamide (1-9) and N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substitue) thioureido]benzenesulfonamide (10-14) derivatives were synthesized from 4-amino-N-(5-methyl-1,3,4-thiadiazol-2-yl)benzenesulfonamide (Sulfamethizole). All new compounds were characterized by elemental analysis and various spectroscopic methods (FTIR, 1H-NMR and MS). These new sulfonamide derivatives were investigated as inhibitors of carbonic anhydrase especially human carbonic anhydrase I and II. The new compounds showed higher activity against the human cytosolic CA I (IC50 values 0.095-15.65 nM) and CA II (IC50 values 0.057-17.95 nM) in comparison with the clinically used CAI inhibitor acetazolamide.
Keywords: Carbonic anhydrase inhibitors, sulfonamide, sulfamethizole, urea and thiourea